Low-resistance target material and preparation method thereof
By doping Mg elements and optimizing the preparation process, the problem of poor conductivity of p-type semiconductor materials is solved, and a low-resistance target with high conductivity and high density is obtained, which is suitable for the application of photoelectric materials.
Patent Information
- Application Number
- CN202411288897.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
The application of existing p-type semiconductor materials in photoelectric materials is limited by resistivity and transmittance, especially their conductivity is poor, which affects the coating performance.
By doping Mg elements and adopting specific preparation processes, including ball mill mixing, cold pressing molding and second-stage sintering, the sintering temperature and pressure conditions are optimized, the resistance of the target is reduced, and its conductivity is improved.
A low-resistance target with high relative density, single crystal structure and good conductivity was obtained, which was low cost and easy to promote.
Smart Images

Figure CN119191832A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of semiconductor materials and relates to a method for preparing a target material, and in particular to a low-resistance target material and a method for preparing the same. Background Art
[0002] At present, most of the transparent conductive oxides used as optoelectronic materials on the market are tin-doped indium trioxide (ITO), aluminum-doped zinc oxide (AZO), fluorine-doped tin dioxide (FTO), etc., and these transparent conductive oxides are all n-type semiconductor materials. The application prospects of p-type semiconductor materials in optoelectronic materials are limited due to the influence of resistivity and transmittance.
[0003] CuCrO2 is a typical p-type semiconductor material with a good optical band gap and high electrical conductivity. However, the electrical conductivity of p-type semiconductors is poorer than that of n-type semiconductors, which affects the performance of subsequent coatings. Summary of the invention
[0004] In view of the defects and shortcomings of the prior art, in a first aspect, the present invention provides a method for preparing a low-resistance target material; in a second aspect, the present invention provides a target material prepared by the above preparation method.
[0005] In a first aspect, the present invention provides a method for preparing a low-resistance target material, comprising the following steps: Step 1, ball-milling cuprous oxide powder, chromium oxide powder, and magnesium oxide powder to obtain a mixed powder; Step 2, the mixed powder is placed in a graphite mold for cold pressing and then heated to 400-500°C in a vacuum atmosphere for a first sintering; then heated to 1020-1100°C for a second sintering to obtain a rough blank; Step 3, pressurizing the rough blank to 30-50 MPa at 1020-1100° C. and maintaining the temperature and pressure for a certain period of time, and then cooling to obtain the low-resistance target material.
[0006] Preferably, in step 1, the mass ratio of cuprous oxide powder, chromium oxide powder and magnesium oxide powder is 1:0.8-1.4:0.1-0.5.
[0007] Preferably, in step 1, the particle sizes of cuprous oxide powder, chromium oxide powder and magnesium oxide powder are all less than 20 μm.
[0008] Preferably, in step 1, the ball milling speed is 20-60 r / min; and the ball milling time is 6-30 h.
[0009] Preferably, in step 2, during cold pressing, the pressurization rate is 0.1-0.6 MPa / min; and the cold pressing pressure is 5-10 MPa.
[0010] Preferably, in step 2, the heating rate of one stage of sintering is 5-10° C. / min; and the sintering time of one stage of sintering is 5-120 min.
[0011] Preferably, in step 2, the heating rate of the second-stage sintering is 3-10° C. / min; and the sintering time of the second-stage sintering is 10-120 min.
[0012] Preferably, in step 3, the pressurization rate is 0.1-0.6 MPa / min; and the time of heat preservation and pressure maintenance is 10-180 min.
[0013] Preferably, in step 3, cooling is natural cooling.
[0014] Preferably, step 3 further includes a processing step of cutting off 0.2-2 mm from the top and bottom surfaces of the low-resistance target material; after observing that the target material is qualified, cutting the side surface of the target material with a cutting depth of 0.2-2 mm.
[0015] In a second aspect, the present invention provides a low-resistance target material prepared by the above preparation method.
[0016] The target material provided by the present invention has a resistance of less than 50Ω▪cm.
[0017] Compared with the prior art, the present invention has the following obvious beneficial effects: (1) The electrical conductivity of p-type semiconductor materials in the prior art is relatively poor compared to that of n-type semiconductor materials. The present invention reduces resistance, increases hole concentration, and enhances electrical conductivity by doping Mg elements, and further improves the electrical conductivity of the target material by combining the preparation process provided by the present invention, thereby obtaining a target material with high relative density, single crystal structure, uniform color, and good electrical conductivity.
[0018] (2) The preparation method provided by the present invention is low-cost and easy to operate, which is conducive to promotion and marketization. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the X-ray diffraction pattern of the target material prepared in Example 1 of the present invention; Figure 2 This is the X-ray diffraction pattern of the target material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0020] The present invention provides the following specific technical solutions.
[0021] In a first aspect, the present invention provides a method for preparing a low-resistance target material; in a second aspect, the present invention provides a target material prepared by the above preparation method.
[0022] In a first aspect, the present invention provides a method for preparing a low-resistance target material, comprising the following steps: Step 1, ball-milling cuprous oxide powder, chromium oxide powder, and magnesium oxide powder to obtain a mixed powder; Step 2, the mixed powder is placed in a graphite mold for cold pressing and then heated to 400-500°C in a vacuum atmosphere for a first sintering; then heated to 1020-1100°C for a second sintering to obtain a rough blank; Step 3, pressurizing the rough blank to 30-50 MPa at 1020-1100° C. and maintaining the temperature and pressure for a certain period of time, and then cooling to obtain the low-resistance target material.
[0023] In the prior art, the CuCrO2 target is a p-type target with a good optical band gap and high conductivity, but the conductivity of a p-type semiconductor is poorer than that of an n-type semiconductor. Therefore, the inventor reduces its resistance by doping Mg elements and increases the hole concentration to enhance the conductivity of the target. Furthermore, the present invention further reduces the resistance of the target and enhances the conductivity by optimizing the preparation process. The cold pressing process can increase the contact area between the powders, which is beneficial to the sintering process, and promotes a more uniform arrangement of the powders during the cold pressing process. If cold pressing is not performed, powder spraying is prone to occur when the powder is pressurized during sintering, requiring a longer sintering time and a higher sintering temperature; if the temperature of a sintering stage is too high, the powder will sinter and react in advance, making it difficult to obtain a high-density target, and cracks are likely to occur; if the temperature of a sintering stage is too low, the rough blank forming effect is poor; if the temperature during hot pressing and heat preservation is low, the material reaction is incomplete, affecting the quality of the target; if the temperature during hot pressing and heat preservation is high, the applied pressure is prone to fracturing the target. In summary, the present invention significantly improves the conductivity of the target material by cooperating with the doping Mg element and the preparation process.
[0024] Preferably, in step 1, the mass ratio of cuprous oxide powder, chromium oxide powder and magnesium oxide powder is 1:0.8-1.4:0.08-0.3.
[0025] The inventors have found that when preparing the target material, if there is too little magnesium, the hole concentration of the target material is low, resulting in a decrease in the resistance of the target material; if there is too much magnesium, more MgCr2O4 is generated in the target material, affecting the performance of the film obtained by subsequent sputtering of the target material. If there is too much copper, the surface of the target material is severely reduced, affecting the quality of the target material; if there is too much chromium, the hot pressing temperature needs to be increased, which is easy to aggravate the reduction of the copper element in the target material, increase the possibility of generating CuCr2O4, and affect the performance of the film obtained by subsequent sputtering of the target material.
[0026] Preferably, in step 1, the particle sizes of cuprous oxide powder, chromium oxide powder and magnesium oxide powder are all less than 20 μm.
[0027] Preferably, in step 1, the ball milling speed is 20-60 r / min; and the ball milling time is 8-30 h.
[0028] Preferably, in step 2, during cold pressing, the pressurization rate is 0.1-0.6 MPa / min; and the cold pressing pressure is 5-10 MPa.
[0029] If the cold pressing rate is too slow, the process time will be extended and the cost will increase; if the cold pressing rate is too fast, the mold will be sprayed with powder, which is not conducive to uniform filling of powder.
[0030] Preferably, in step 2, the heating rate of one stage of sintering is 5-10° C. / min; and the sintering time of one stage of sintering is 10-60 min.
[0031] In one stage of sintering, if the heating rate is too fast, it is easy to cause uneven temperature field; if the heating rate is too slow, the process time will be extended and the cost will be increased. If the holding time is too short, the uniform temperature field will not be achieved; if the holding time is too long, the powder may be sintered prematurely and it is difficult to be dense.
[0032] Preferably, in step 2, the heating rate of the second-stage sintering is 5-15° C. / min; and the sintering time of the second-stage sintering is 10-60 min.
[0033] In the second stage sintering, if the heating rate is too fast or the holding time is too short, the temperature field will be uneven, resulting in different degrees of powder sintering; if the heating rate is too slow and the heating time becomes longer, it is easy to cause the powder to sinter prematurely, while causing an increase in costs.
[0034] Preferably, in step 3, the pressurization rate is 0.1-0.6 MPa / min; and the time of heat preservation and pressure maintenance is 20-120 min.
[0035] If the pressurization rate is too fast during the hot pressing process, it is not conducive to the uniform distribution of the density of the compact. If the pressurization rate is too slow, the process time will be extended and the cost will increase. If the holding time is too short, the densification degree of the target blank is not enough. If the holding time is too long, the target blank is easy to be cracked.
[0036] Preferably, in step 3, cooling is natural cooling.
[0037] Preferably, step 3 further includes a processing step of cutting off 0.2-2 mm from the top and bottom surfaces of the low-resistance target material; after observing that the target material is qualified, cutting the side surface of the target material with a cutting depth of 0.2-2 mm.
[0038] During the hot pressing process, graphite paper is placed on the contact surface of the target material and the mold. Graphite paper can easily reduce the oxides on the surface of the target material. The reduced part can be removed by cutting the surface of the target material. The entire target material needs to be processed. First, one side is cut out and the color and texture of the cut surface of the target material are observed to be uniform, then the other sides of the target material can be cut. If the cut surface has uneven color, pores, and uneven texture, it means that the target material is unqualified and the target material enters the waste process.
[0039] In a second aspect, the present invention provides a low-resistance target material prepared by the above preparation method.
[0040] Preferably, the resistance of the target material is less than 50Ω▪cm.
[0041] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.
[0042] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0044] Embodiment 1: A method for preparing a low-resistance target material comprises the following steps: Step 1, mixing cuprous oxide powder, chromium oxide powder and magnesium oxide powder in a mass ratio of 1:1:0.1 and ball milling at a ball milling speed of 60 r / min for 16 h to obtain a mixed powder.
[0045] Step 2: Load the mixed powder into a graphite mold, then transfer the graphite mold to a hot pressing sintering furnace, increase the pressure at a pressure rate of 0.1 MPa / min to 5 MPa, cold-press the mixed powder in the graphite mold to form it, then evacuate the hot pressing sintering furnace to less than 10 Pa and enter the first sintering stage, heat it to 420°C at a heating rate of 5°C / min, and keep it warm for 30 minutes; enter the second sintering stage, heat it to 1020°C at a heating rate of 5°C / min, and keep it warm for 10 minutes to obtain a rough blank.
[0046] Step 3, continue to pressurize the rough blank in the graphite mold at 1020°C at a pressure rate of 0.1MPa / min to 40MPa, and keep the temperature and pressure for 1h, then cool naturally, and demold to obtain a low-resistance target material.
[0047] Step 4, fix the low-resistance target on a CNC milling machine, use a resin diamond grinding wheel to mill the surface, the diamond grinding wheel is 200 mesh, the rotation speed is 800r / min, the top and bottom surfaces are both removed by more than 1mm, and after cleaning and drying the target, detection and analysis are performed.
[0048] Embodiment 2: A method for preparing a low-resistance target material comprises the following steps: Step 1, mixing cuprous oxide powder, chromium oxide powder and magnesium oxide powder in a mass ratio of 1:0.8:0.1 and ball milling at a ball milling speed of 20 r / min for 30 h to obtain a mixed powder.
[0049] Step 2: Load the mixed powder into a graphite mold, then transfer the graphite mold to a hot pressing sintering furnace, increase the pressure at a pressure rate of 0.6 MPa / min to 10 MPa, cold-press the mixed powder in the graphite mold to form it, then evacuate the hot pressing sintering furnace to less than 10 Pa and enter the first sintering stage, heat it to 460°C at a heating rate of 10°C / min, and keep it warm for 10 minutes; enter the second sintering stage, heat it to 1100°C at a heating rate of 5°C / min, and keep it warm for 35 minutes to obtain a rough blank.
[0050] Step 3, continue to pressurize the rough blank in the graphite mold at 1100°C at a pressure rate of 0.6MPa / min to 30MPa, and keep the temperature and pressure for 2h, then cool naturally, and demold to obtain a low-resistance target material.
[0051] Step 4, fix the low-resistance target on a CNC milling machine, use a resin diamond grinding wheel to mill the surface, the diamond grinding wheel is 200 mesh, the rotation speed is 800r / min, the top and bottom surfaces are both removed by more than 1mm, and after cleaning and drying the target, detection and analysis are performed.
[0052] Embodiment 3: A method for preparing a low-resistance target material comprises the following steps: Step 1, mixing cuprous oxide powder, chromium oxide powder and magnesium oxide powder in a mass ratio of 1:1.4:0.3 and ball milling at a ball milling speed of 40 r / min for 8 h to obtain a mixed powder.
[0053] Step 2: Load the mixed powder into a graphite mold, then transfer the graphite mold to a hot pressing sintering furnace, increase the pressure at a pressure rate of 0.3 MPa / min to 7 MPa, cold-press the mixed powder in the graphite mold to form it, and then evacuate the hot pressing sintering furnace to less than 10 Pa before entering the first sintering stage, heating the temperature to 500°C at a heating rate of 10°C / min, and keeping it warm for 120 minutes; entering the second sintering stage, heating the temperature to 1040°C at a heating rate of 15°C / min, and keeping it warm for 60 minutes to obtain a rough blank.
[0054] Step 3, continue to pressurize the rough blank in the graphite mold at 1040°C at a pressure rate of 0.3MPa / min to 50MPa, and keep the temperature and pressure for 20 minutes, then cool naturally and demold to obtain a low-resistance target material.
[0055] Step 4, fix the low-resistance target on a CNC milling machine, use a resin diamond grinding wheel to mill the surface, the diamond grinding wheel is 200 mesh, the rotation speed is 800r / min, the top and bottom surfaces are both removed by more than 1mm, and after cleaning and drying the target, detection and analysis are performed.
[0056] Comparative Example 1: The difference from Example 1 is that the sintering process in step 2 is a one-stage sintering at a temperature of 1020°C.
[0057] Comparative Example 2: The difference from Example 1 is that the hot pressing temperature in step 3 is 1000°C.
[0058] Comparative Example 3: The difference from Example 1 is that the hot pressing temperature in step 3 is 1150°C.
[0059] Comparative Example 4: The difference from Example 1 is that magnesium oxide powder is not added in step 1.
[0060] The target materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to relative density tests and electrical conductivity tests, wherein the relative density was directly tested using the traditional Archimedean method, and the electrical conductivity was tested using a four-probe test.
[0061] Table 1 - Data of relative density test and conductivity test of target materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 By comparing the test data of Example 1 and Comparative Example 1, it can be seen that the present invention can significantly improve the relative density and conductivity of the target material through the two-stage sintering process; by comparing the test data of Example 1 and Comparative Example 2 and Comparative Example 3, it can be seen that if the temperature in the heat preservation and pressure holding stage is too high or too low, it will affect the relative density and conductivity of the target material; by comparing the test data of Example 1 and Comparative Example 4, it can be seen that the present invention can significantly improve the relative density and conductivity of the target material by adding the Mg element. Combined with the test data in Table 1, it can be seen that if only the Mg element is doped or only two-stage sintering is performed, the low-resistance, high-density target material cannot be obtained, which can further prove that in the technical solution provided by the present invention, the doping of the Mg element and the preparation process cooperate with each other to obtain a P-type semiconductor target material with good conductivity, high relative density and high purity.
[0062] Figure 1 is the X-ray diffraction pattern of the target material prepared in Example 1 of the present invention, Figure 2 is the X-ray diffraction pattern of the target material prepared in Example 2 of the present invention; Figure 1 and Figure 2It can be seen that the diffraction characteristic peaks of the target materials prepared in Example 1 and Example 2 correspond well to the XRD diffraction characteristic peaks of CuCrO2, and there are no impurity peaks, indicating that the preparation method provided by the present invention successfully prepares a semiconductor material with high purity and a single crystal structure.
[0063] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a low resistance target material, characterized in that: The steps include: Step 1, ball-milling cuprous oxide powder, chromium oxide powder, and magnesium oxide powder to obtain a mixed powder; Step 2, the mixed powder is placed in a graphite mold for cold pressing and then heated to 400-500°C in a vacuum atmosphere for a first sintering; then heated to 1020-1100°C for a second sintering to obtain a rough blank; Step 3, pressurizing the rough blank to 30-50 MPa at 1020-1100° C. and maintaining the temperature and pressure for a certain period of time, and then cooling to obtain the low-resistance target material.
2. The method for preparing a low resistance target material according to claim 1, characterized in that: In step 1, the mass ratio of cuprous oxide powder, chromium oxide powder and magnesium oxide powder is 1:0.8-1.4:0.1-0.
5.
3. The method for preparing a low resistance target material according to claim 1 or 2, characterized in that: In step 2, during cold pressing, the pressurization rate is 0.1~0.6MPa / min; the cold pressing pressure is 5~10MPa.
4. The method for preparing a low resistance target material according to claim 1, characterized in that: In step 2, the heating rate of the first sintering is 5-10°C / min; the sintering time of the first sintering is 5-120min; the heating rate of the second sintering is 3-10°C / min; the sintering time of the second sintering is 10-120min.
5. The method for preparing a low resistance target material according to claim 1 or 4, characterized in that: In step 3, the pressurization rate is 0.1-0.6 MPa / min; the heat preservation and pressure holding time is 10-180 min.
6. The method for preparing a low resistance target material according to claim 1, characterized in that: Step 3 also includes a processing step of cutting off 0.2 to 2 mm from the top, bottom and side surfaces of the low-resistance target material.
7. The method for preparing a low resistance target material according to claim 1, characterized in that: In step 1, the particle sizes of cuprous oxide powder, chromium oxide powder and magnesium oxide powder are all less than 20 μm; the ball milling speed is 20-60 r / min; and the ball milling time is 6-30 h.
8. The method for preparing a low resistance target material according to claim 1, characterized in that: In step 3, the cooling is natural cooling.
9. A low resistance target material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
10. The low-resistance target material according to claim 9, characterized in that: The electrical resistance of the target material is less than 50Ω▪cm.
Citation Information
Patent Citations
Method for preparing transparent conductive oxide thin film with P-type delafossite structure
CN101215702A
Manufacturing method of tungsten-titanium target material and manufacturing method of tungsten-titanium target material combination
CN103691953A
Cadmium stannate target material and preparation method thereof
CN105585317A
P-type CrMCuO amorphous oxide semiconductor thin film and preparation method thereof
CN106711201A
Ceramic target and preparation method thereof
CN110171974A
